Spiritualitas Well-Being Abdi Dalem Lansia Pura Mangkunegaran Surakarta - Rahmawati Putri, Aisyah; Kutub Hardew, Ayatullah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Abdi Dalem" refer to individuals that dedicated this life to serving in the palace. They are responsible for assisting in the operational activities within the palace, and additionally, they play a role as cultural servants within their respective regions. "Abdi Dalem" serving at Pura Mangkunegaran in Surakarta includes individuals ranging from the young to the elderly. Despite the limitations faced by the elderly, such as the decline in various functions-physically, psychologically, socially, and economically-they remain determined to continue their service at Pura Mangkunegaran in Surakarta. Therefore, to understand the well-being spirituality of these elderly "Abdi Dalem," it is essential to conduct research to uncover the phenomenon essence that shapes their life experiences. This research used a semi-structured interview method, with three subjects selected through purposive sampling. The criteria for the subjects include being an active "Abdi Dalem" at Pura Mangkunegaran for a minimum of 30 years and being at least 60 years old. Data analysis employs interpretative phenomenological analysis (IPA). The result of this research indicate that the subjects had a well-being spirituality predominantly influenced by the existential dimension. This dimension involves the relationship between the individual and society, where the crucial role of self-concept affects the well-being spirituality of the elderly. Keywords: Abdi Dalem; Eldery; and Well-being spirituality